MODEL PENGAMBILAN KEPUTUSAN DESENTRALISASI PADA UNIT LEMBAGA KEUANGAN - Komala Ardiyani; M Maulidin Fachrur (LPPM Universitas Pekalongan, 2012)
This study aims to determine the model of decentralized decisions on unit financial institutions and decentralized decision model differences between banks and non-banks. The decision-making in the expansion areas include marketing, determination of new assets, sales and hiring priorities. Research data obtained by sending questionnaires to the respondents. The respondents of this study is the unit managers of financial institutions. Forty-eight (48) questionnaires were used in data processing. The data is processed using different test t-test. These results prove that the decentralized decision n occurs when the unit is to expand new market areas and prioritize sales, while other decisions in the hands of central management. The results of different test t-test states that there are differences between the decentralized decision model two types of financial institutions.Keywords: Decisiondecentralization, financial institutionsunit.